2015
DOI: 10.1080/07900627.2015.1023892
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Syrian conflict on irrigated agriculture in the Orontes Basin

Abstract: The impact of conflict on irrigated agriculture and consequently summer crop production within conflict-affected agricultural lands was observed in the Orontes Basin. Water and energy use were reconfigured through a transition from rainfed to irrigated agricultural production over the past 20 years, but have been disrupted as the Syrian war has unfolded since 2011. Remotely sensed vegetation indices were used to determine irrigated summer crop yields during the year 2013. Findings suggest that irrigated agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…For example, the Syrian crisis led to a decrease in irrigated agriculture in Southern Syria, associated with changes in the way Syrians managed their reservoirs, which caused an increase in the flow of downstream Yarmouk river to Jordan (Müller et al 2016). A remotesensing based study conducted on the Syrian portion of the Orontes basin showed a severe drop in irrigated agricultural production (Jaafar et al 2015), indicating a lower usage of both surface and groundwater in the Syrian parts of the basin in contrast to the Lebanese part were water use had been reported to increase (Jaafar et al 2016;King and Jaafar 2015).…”
Section: Impact Of Refugees' Crisis On the Water In Host Countriesmentioning
confidence: 99%
“…For example, the Syrian crisis led to a decrease in irrigated agriculture in Southern Syria, associated with changes in the way Syrians managed their reservoirs, which caused an increase in the flow of downstream Yarmouk river to Jordan (Müller et al 2016). A remotesensing based study conducted on the Syrian portion of the Orontes basin showed a severe drop in irrigated agricultural production (Jaafar et al 2015), indicating a lower usage of both surface and groundwater in the Syrian parts of the basin in contrast to the Lebanese part were water use had been reported to increase (Jaafar et al 2016;King and Jaafar 2015).…”
Section: Impact Of Refugees' Crisis On the Water In Host Countriesmentioning
confidence: 99%
“…Grains have also been confiscated from farmers who fled the area, as well as lands and livestock. Recently, there have been studies on agricultural transformation due to armed conflict in Syria and Iraq (Jaafar et al 2015, Jaafar andWoertz 2016). In Syria, irrigated agricultural production has been reported to have dropped by between 15% and 30% in the Orontes river basin from 2000 to 2013 (Jaafar et al 2015).…”
Section: Study Areamentioning
confidence: 99%
“…Recently, there have been studies on agricultural transformation due to armed conflict in Syria and Iraq (Jaafar et al 2015, Jaafar andWoertz 2016). In Syria, irrigated agricultural production has been reported to have dropped by between 15% and 30% in the Orontes river basin from 2000 to 2013 (Jaafar et al 2015). Another study though observed stability in agricultural production in areas controlled by the IS, despite expected decreases in cultivated lands due to population outflow from conflict areas (Jaafar and Woertz 2016).…”
Section: Study Areamentioning
confidence: 99%
“…Compared with the conventional surface flooding irrigation commonly used in China, drip irrigation is more efficient in reduction of energy consumption and carbon emissions [77]. Significant efforts should be also made by policy makers regarding identification of advanced water resource management to promote water saving irrigation, e.g., remote sensing and satellite imagery are useful to identify losses in agricultural productivity by assessing agricultural water use, which supports better agricultural planning [78]. Besides, a number of policy instruments, such as pricing strategy, economic sanctions, financial subsidies, etc., may give rise to internalization of the external cost of water, thus to drive development of less water intensive industries and services [7,79].…”
Section: Discussionmentioning
confidence: 99%